Byron - Doherty, Francis M . (Literature in perspective, 1968)
George Gordon Lord Byron, the sixth of the title, has always fascinated biographers (and he has many), though his poetry has tended to be rather more neglected by the critics. This is not to say that his life, a most romantic one by anyone's standard, is more entertaining than his writing. It is not as simple as that